2008
DOI: 10.1182/blood-2007-07-104141
|View full text |Cite
|
Sign up to set email alerts
|

TLR9 engagement on CD4 T lymphocytes represses γ-radiation–induced apoptosis through activation of checkpoint kinase response elements

Abstract: T cell-based therapies have much promise in cancer treatment. This approach may be enhanced if used in combination with radiotherapy provided that tumorspecific T cells can be protected against the effects of radiotherapy. Previously, we demonstrated that administration of TLR9 ligand into mice decreased activation-and serum deprivation-induced cell death in T cells. We hypothesized that TLR9 engagement on T lymphocytes decreased apoptosis after cellular stress. We show that TLR9 engagement on murine CD4 T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 69 publications
4
38
0
Order By: Relevance
“…Furthermore, studies by several groups, including ours, have demonstrated that activating MyD88/IRAK signaling via TLR engagement on CD4 Th cells or CD8 T cells substantially enhances proliferation (5,(21)(22)(23)(24)(25). Engagement of TLRs has also been shown to prolong cell survival, which correlates with increased expression levels of BCL-xL and BCL2 (26,27), as well as A1, and reduced levels of BIM (24,26,27).…”
Section: Introductionmentioning
confidence: 69%
“…Furthermore, studies by several groups, including ours, have demonstrated that activating MyD88/IRAK signaling via TLR engagement on CD4 Th cells or CD8 T cells substantially enhances proliferation (5,(21)(22)(23)(24)(25). Engagement of TLRs has also been shown to prolong cell survival, which correlates with increased expression levels of BCL-xL and BCL2 (26,27), as well as A1, and reduced levels of BIM (24,26,27).…”
Section: Introductionmentioning
confidence: 69%
“…The engagement of TLRs on APCs is a critical step for the optimal activation and expansion of T cells. However, several reports indicate that the ligation of specific TLRs directly on primary CD4 and CD8 T cells 6,7,[11][12][13]28,29 or T-cell lines 30 can enhance their responses. The study reported here was aimed at gaining a better understanding of the molecular mechanisms involved in the costimulatory effects of TLR-MyD88 activation in CD8 T cells.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 However, recent advances by several groups, including ours, indicate that the adjuvant effects of certain TLR agonists may also be attributed to the activation of TLRs and the TLR adapter molecule myeloid differentiation factor (MyD88) directly in T cells. Both CD4 [3][4][5][6][7][8][9][10][11]12,13 T cells express functional TLRs. In CD8 T cells, concomitant engagement of the T-cell receptor (TCR) and TLR3 enhanced interferon-␥ (IFN-␥) production, 10 whereas TLR2 engagement on CD8 T cells increased the expression levels of granzyme B in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Another type of DNA damage-causing radiation, gamma irradiation, results in double-strand breaks that cannot be repaired using a complementary template; it is associated with mutagenesis and chromosome abnormalities that often lead to cell death. Repair of both UV and gamma irradiation damage was shown to be altered in the presence of endosomal TLR agonists (12,13), implying that both the NER and double-strand breaks repair complex may be affected by the status of TLR activation. In this study, we focus on DNA damage caused by UVR in the form of CBPDs, which requires NER machinery to be excised and repaired.…”
mentioning
confidence: 99%